Geometric AR-based pedagogical module is beneficial: Affecting factors from the lens of Malaysian mathematics secondary school teachers - Faridah Hanim Yahya, Mohd Ridhuan Mohd Jamil, Mohd Muslim Md Zalli (Tanjung Malim, 2024)
Geometric AR-based pedagogical module is beneficial: Affecting factors from the lens of Malaysian mathematics secondary school teachers by Faridah Hanim Yahya, Mohd Ridhuan Mohd Jamil, Mohd Muslim Md Zalli